2010
DOI: 10.5204/jld.v4i1.68
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Blending In Virtual Microscopy

Abstract: Virtual microscopy (VM) is a relatively new technology that transforms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…found that 81.6% of respondents believed VM solved the problems they had experienced when using the optical microscope. A frequent student complaint about optical microscopes is that they are difficult to use and cause eye strain . Perhaps the principal advantage of VM is that it diminishes the frustrations some students experience in using the optical microscope and effectively eliminates this skill barrier as an impediment to effective learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…found that 81.6% of respondents believed VM solved the problems they had experienced when using the optical microscope. A frequent student complaint about optical microscopes is that they are difficult to use and cause eye strain . Perhaps the principal advantage of VM is that it diminishes the frustrations some students experience in using the optical microscope and effectively eliminates this skill barrier as an impediment to effective learning.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al, 43 Krippendorf & Lough, 52 Boutonnat et al, 66 Glatz-Krieger et al, 67 Kumar et al, 68 Mills et al, 53 Neel et al, 7 Scoville & Buskirk, 11 Braun & Kearns, 15 Farah & Maybury, 6 Weaker & Herbert, 47 Maybury & Farah, 44 Sivamalai et al, 38 Camparo et al, 5 Bonser et al, 64 Bowa & Anderson, 65 Kogan et al 51 Slides selected for their educational quality can be viewed by multiple students simultaneously (including slides that were once too scarce or too valuable to be used) Blake et al, 46 Dee et al, 70 Kumar et al, 43 Krippendorf & Lough, 52 Boutonnat et al, 66 Glatz-Krieger et al, 67 Mills et al, 53 Pinder et al, 10 Farah & Maybury, 6 Husmann et al, 8 Weaker & Herbert, 47 F onyad et al, 50 Fontelo et al, 69 Solberg, 54 Bonser et al, 64 Kogan et al 51 Virtual slides can be accessed outside the classroom (anytime/anywhere) Dee et al, 70 Kumar et al, 43 Mills et al, 53 Pinder et al, 10 Farah & Maybury, 6 Maybury & Farah, 44 Sivamalai et al, 38 McCready & Jham, 71 Kogan et al, 51 Tian et al…”
Section: Themes Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was expected as collaborative WSI annotation was designed to increase student engagement, which is positively correlated with perceptions of improved understanding [35, 7, 8, 12, 38, 41, 47, 48]. …”
Section: Discussionmentioning
confidence: 99%
“…annotations [36, 8, 12, 21]. Such annotations may enhance learning by promoting longer and more meaningful interactions between students and learning resources [21].…”
Section: Introductionmentioning
confidence: 99%